Critically Queer Yet Politically Affirmative Engagements with Human Rights - Remzi Orkun Güner (Annales de la Faculté de Droit d’Istanbul)
Considering recent queer engagements with international human rights, this article argues that emerging attempts at queering rights have often resulted in framing queer critique into the normativity of human rights. This article critiques this tendency, suggesting that queer engagement with rights can be critical yet (potentially) affirmative. It shows that queer critique, understood as non-essentialist politics, can contribute to contemporary critical human rights studies and their analyses of identity-producing functions of rights. In this way, the paper engages not only with the subject paradox of the rights discourse but also with queer responses to identity-based rights claims. I argue that queer critiques, shifting the focus from ontology to politics, encourage an affirmative engagement with framings of rights by considering identities as political claims, understanding rights not in ontological terms but as instruments for shifting temporary strategies in practice. The arena of rights, a site where debates about the definitions of human are contested, is a crucial space for deploying non-essentialist politics. In this context, the article refers to queer as a critical method in deploying rights to reduce the disciplinary effects of identities, helping us to free ourselves, our engagements with others, and politics from the eyes of the Normative.